The Impact of Digital Information Systems on Technology-Based Service Quality - Erwin Teguh Arujisaputra; Moch. Edy Purwanto; Yurika Yurika (Jurnal Ragam Pengabdian, 2026)
This study explores the impact of digital information systems on the quality of technology-based services through a qualitative literature review. Utilizing a library research approach, the study systematically analyzes scholarly publications to identify key mechanisms through which digital information systems influence service outcomes. The findings reveal that these systems enhance service efficiency by streamlining processes and reducing manual tasks, improve information accessibility and transparency for users, ensure system reliability and consistency, and strengthen user experience through intuitive and responsive platforms. Organizational capability and employee digital competence are found to be critical factors in realizing the full potential of digital systems, while digital service innovation enables organizations to develop flexible, personalized, and data-driven service models. The synthesis of these findings highlights that digital information systems act as central enablers of service quality, interacting with organizational structures, technological infrastructure, and human competencies to improve operational performance and user satisfaction. The study provides a comprehensive framework for understanding the multi-dimensional effects of digital information systems on technology-based service quality, offering insights for both academics and practitioners seeking to optimize digital service delivery in modern organizations.